Symptoms in the pharmacy : a guide to the management of common illnesses - Blenkinsopp, Alison; Paxton, Paul; Blenkinsopp, John (Hoboken : Wiley, 2014)
Symptoms in the Pharmacy presents a guide to the management of common symptoms seen in the pharmacy, with advice from an author team that includes both pharmacists and GPs. With the continued emphasis on the pharmacist$1 (Bs role as a $1 (Bfirst port of call$1 (Bin response to symptoms, the need for effective communication and interpersonal skills remains paramount. This book provides the pharmacist with the appropriate techniques for gathering information to meet the needs of patient safety in a way that is acceptable to the public. Case studies and comments from the pharmacist$1 (Bs and doctor$1 (Bs perspectis
Preface, vi Introduction: How to Use This Book, 1 Respiratory Problems Colds and flu, 19 Cough, 33 Sore throat, 45 Allergic rhinitis (hay fever), 53 Respiratory symptoms for direct referral, 62 Gastrointestinal Tract Problems Mouth ulcers, 69 Heartburn, 76 Indigestion, 85 Nausea and vomiting, 95 Motion sickness and its prevention, 98 Constipation, 102 Diarrhoea, 112 Irritable bowel syndrome, 124 Haemorrhoids, 132 Skin Conditions Eczema/dermatitis, 143 Acne, 153 Athlete's foot, 159 Cold sores, 167 Warts and verrucae, 172 Scabies, 178 Dandruff, 182 Psoriasis, 186 Painful Conditions Headache, 193 Musculoskeletal problems, 210 Women's Health Cystitis, 225 Dysmenorrhoea, 234 Menorrhagia, 243 Vaginal thrush, 246 Emergency hormonal contraception, 255 Common symptoms in pregnancy, 263 Men's Health Benign prostatic hyperplasia, 269 Hair loss, 274 Eye and Ear Problems Eye problems: the painful red eye, 281 Common ear problems, 289 Childhood Conditions Illnesses affecting infants and children up to 16 years, 297 Colic, 303 Teething, 306 Napkin rash, 307 Head lice, 313 Threadworms (pinworms), 319 Oral thrush, 323 Insomnia Difficulty sleeping, 331 Prevention of Heart Disease Prevention of heart disease, 343 Appendix: Summary of Symptoms for Direct Referral, 359 Index, 361 Colour plates are found facing page 184 and 185.
Previous edition: 2009.
Includes bibliographical references and index.
Keywords: Chemotherapy; Pharmaceutical services; Diagnosis